FAKTOR YANG MEMPENGARUHI CSRD PADA PERUSAHAAN CONSUMER NON-CYCLICAL PERIODE 2019-2021 - Felix Colim; Rosmita Rasyid (Fakultas Ekonomi, Universitas Tarumanagara, 2026)
This research was made with the aim of studying and obtaining empirical evidence regarding the iinfluence, profitability, liquidity, firm size, and solvency on the value of CSRD of non-cyclical consumer companies listed on the IDX for the 2019-2021 periods. The study used secondary data obtained at www.idx.co.id, samples that match the criteria were taken from as many as 30 companies. This research used a purposive sampling method. The techniques that were used for data analysis were descriptive statistics and the method for testing the hypothesis was the regression method which was processed by Eviews12. CSRD uses the GRI-4 standard. This study reveals that profitability, firm size, and solvency have significant effects on the value of CSRD while the current ratio has no significant effects on the value of CSRD. The implications of this study are to pay attention to profitability, firm size, and solvency to improve the value of CSRD.